A strobe multicenter descriptive study of 55 infectious aortitis. Issue 40 (2nd October 2020) - Journeau, Louis; de la Chapelle, Marine; Guimard, Thomas; Ferfar, Yasmina; Saadoun, David; Mahé, Isabelle; Castier, Yves; Montravers, Philippe; Lescure, Xavier; Van Gysel, Damien; Asseray, Nathalie; Lascarrou, Jean-Baptiste; et al.
Abstract : Abstract: Infectious aortitis (IA) is a rare and severe disease. The treatment classically associates open surgery with prolonged antibiotic therapy. This study aimed to describe clinical characteristics, medical and surgical supports in a large and current series of IA. We conducted a retrospective multicenter study of native aorta IA, between 2000 and 2019. Inclusion criteria were the presence of a microorganism on blood culture, aortic sample or any other validated technique and structural anomaly in imaging. We included 55 patients (85% men), with a median age of 65. Microbiology data substantially differed from previous studies with 12 Gram-negative rods IA, of which only 3 due to Salmonella spp ., 24 Gram-positive cocci IA of which 12 Streptococcus spp., and 18 IA due to intracellular growth and/or fastidious microorganisms, of which 8 Coxiella burnetii, 3 Treponema pallidum, and 5 tuberculosis suspicious cases. Fifteen patients (27%) presented with thoracic IA, 31 (56%) with abdominal IA, and 9 (16%) with thoraco-abdominal IA. Eight patients had no surgery, 41 underwent open surgery, only 4 endovascular aneurysm repair, and 2 a combination of these 2 techniques. Nine patients died before 1-month follow-up. There was no difference in the mortality rate between the different types of germ or localization of IA. The variety of germs involved in IA increases. Positron emission tomography-computed tomography scan is a very useful tool for diagnosis. Surgery is still mainly done in open approach and a prospective multicenter study seems necessary to better determine the place of endovascular aneurysm repair versus open surgery. Abstract : Supplemental Digital Content is available in the text